Fiscal Policy, Economic Diversification and Economic Growth in Nigeria an Analysis on The Long Run Relationship - Arasomwan Kenneth Onaiwu; Samuel Oweh Abang; Omang Nkechi Stella; Ayodele Oluwafemi (Generasi Sains Indonesia, 2024)
Nigeria’s fiscal policy has largely centered on short-term objectives such as revenue generation, with inadequate focus on long-term structural reforms. The economy remains characterized by an inefficient tax system and a persistent dependence on oil revenue despite efforts toward diversification. This study investigates the impact of fiscal policy, economic diversification, and economic growth in Nigeria using annual time-series data from the Central Bank of Nigeria, National Bureau of Statistics, and World Bank covering 1984–2023. Employing descriptive statistics, the Augmented Dickey-Fuller and Phillips-Perron unit root tests, and the ARDL model, the study uses real GDP as the dependent variable and tax, government expenditure, domestic debt, gross fixed capital formation, and diversification index as independent variables. The results indicate that a 10% increase in tax, government expenditure, and diversification index leads to a 0.76%, 1.31%, and 0.84% rise in economic growth, respectively, while a 10% rise in domestic debt reduces growth by 2.69%. The findings show that tax, domestic debt, and diversification index significantly influence growth. Hence, the study recommends strengthening tax mobilization to reduce dependence on oil revenues and enhance macroeconomic stability.